Pengembangan Model Pembelajaran Nomor Lempar Berbasis Permainan di Sekolah Dasar: (The delevelopment of Number Through Learning Model Game-Based in Primary Schools) - Sari, Afriana; Sukirno, Sukirno; Waluyo, Waluyo (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2020)
This development research aims to produce a learning model for game-based or turbo-based learning that can improve students' motivation and ability in the basic motion of throwing numbers.Stages of teaching material development conducted by researchers based on the stages of research development or development research. The results of the validation at the small group stage regarding the quality of the learning model have entered into the